Chromosome‐scale genome assembly of areca palm (Areca catechu). (29th June 2021) - Yang, Yaodong; Huang, Liyun; Xu, Chunyan; Qi, Lan; Wu, Zhangyan; Li, Jia; Chen, Haixin; Wu, Yi; Fu, Tao; Zhu, Hui; Saand, Mumtaz Ali; Li, Jing; et al.
Abstract: Areca palm ( Areca catechu L.; family Arecaceae) is an important tropical medicinal crop and is also used for masticatory and religious purposes in Asia. Improvements to areca properties made by traditional breeding tools have been very slow, and further advances in its cultivation and practical use require genomic information, which is still unavailable. Here, we present a chromosome‐scale reference genome assembly for areca by combining Illumina and PacBio data with Hi‐C mapping technologies, covering the predicted A. catechu genome length (2.59 Gb, variety "Reyan#1") to an estimated 240× read depth. The assembly was 2.51 Gb in length with a scaffold N50 of 1.7Mb. The scaffolds were then further assembled into 16 pseudochromosomes, with an N50 of 172 Mb. Transposable elements comprised 80.37% of the areca genome, and 68.68% of them were long‐terminal repeat retrotransposon elements. The areca palm genome was predicted to harbour 31, 571 protein‐coding genes and overall, 92.92% of genes were functionally annotated, including enriched and expanded families of genes responsible for biosynthesis of flavonoid, anthocyanin, monoterpenoid and their derivatives. Comparative analyses indicated that A. catechu probably diverged from its close relatives Elaeis guineensis and Cocos nucifera approximately 50.3 million years ago (Ma). Two whole genome duplication events in areca palm were found to be shared by palms and monocots, respectively. This genome assembly and associated resources represents an important addition to the palm genomics community and will be a valuable resource that will facilitate areca palm breeding and improve our understanding of areca palm biology and evolution.